Political institutions and economic development: a local spatial analysis for Brazil - Suzuki, William Yasuhiko Nagai (2020)
Political institutions, characterized by North and Thomas (1973) and Acemoglu et al. (2001), are an essential component to explain economic development. The objective of this study is to measure the spatial heterogeneity of the relationship between political institutions and development. For this, we use a spatial moving window method applied to weighted regressions, called Geographically Weighted Regression (GWR), proposed in Fotheringham et al. (2002). In spatial econometrics and global statistical analysis, the common assumption is that the DGP (Data Generating Process) is homogeneous for the whole map or sample. On the other hand, the advantage of the local statistical analysis is that we can estimate the spatially non-stationary DGP underlying the map. Overall we find evidence that political institutions increase economic development. However, local statistical analysis shows that for many parts of Brazil the effect is null or even negative. We present maps indicating where the relationship is positive, negative, and non-significant. The dataset is a spatial cross-section on the municipalities of Brazil for the year 2000.